2020
DOI: 10.1111/jar.12712
|View full text |Cite
|
Sign up to set email alerts
|

Australians with intellectual disability share their experiences of retirement from mainstream employment

Abstract: Background As part of a larger study exploring the transition to retirement for people with intellectual disability from a working life in mainstream employment, this paper reports on retirement from the perspective of those who have already retired. Method Semi‐structured interviews were undertaken with five Australian retirees with intellectual disability. Data were analysed using grounded theory methodology. Employment service records provided background information on participants' employment and supports.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 55 publications
(76 reference statements)
0
14
0
Order By: Relevance
“…Bill's view that "I've got the years in," and Robert's 70th birthday are examples. Australian retirement research has reported similar findings (Brotherton, 2022;Brotherton et al, 2020).…”
Section: Milestonesmentioning
confidence: 64%
See 3 more Smart Citations
“…Bill's view that "I've got the years in," and Robert's 70th birthday are examples. Australian retirement research has reported similar findings (Brotherton, 2022;Brotherton et al, 2020).…”
Section: Milestonesmentioning
confidence: 64%
“…Our findings highlight the need for an increased focus on retirement planning that is person-centered supports individual choice (Brotherton, 2022;Brotherton et al, 2020). Some participants retired in their mid-forties, so this planning should begin early.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…With impairment, work- or travel-related aspects of mobility (e.g., walking long distances, using stairs, catching buses) become more difficult or impossible. Brotherton, Stancliffe, Wilson, and O’Loughlin (2019) reported that a number of older Australians with ID and many years’ experience of community employment retired because their health and mobility made work tasks and/or travel to work via public transportation difficult or unsafe. For example, four of the five participants had stopped traveling to work by public transportation before they retired.…”
Section: Discussionmentioning
confidence: 99%